Climate-wise models of biomass productivity for hybrid poplar clones in Europe - Bianchi, Simone; Lee, Daesung; Bergante, Sara; Facciotto, Gianni; Hynynen, Jari; Nervo, Giuseppe (Italian Society of Sivilculture and Forest Ecology (SISEF), 2023)
Renewable bioenergy has the potential to contribute sustainably to the energy sector. Forestry is the main source of biomass for energy in Europe, and poplar (genus Populus) is widely used for short rotation coppice (SRC). Many studies have assessed poplar clones’ productivity but there is a lack of regional studies and links with the climate. We investigated the biomass productivity of twenty hybrid poplar clones for SRC. Clones were planted in sixteen locations across nine countries in Europe, although not all clones were replicated in all locations. In each location, clones were planted in three replicated plots. All plots were harvested after four years, and the aboveground dry biomass estimated. We fitted clone-specific linear mixed models of total aboveground dry biomass production at plot level as function of climatic variables. For many clones (eight) only annual heat moisture deficit negatively affected productivity, in few cases (3) together with a quadratic term for a smoother relationship. In some other clones (five) only the mean summer precipitation positively and linearly affected productivity. On average, the variance explained by the fixed effects in those models was 56%. For the remaining clones (seven), no climate variables resulted significant. Our study explicitly investigated the quantitative link between water availability and poplar SRC productivity, one of the most important known factors but not often studied with a modelling approach. Further, we show the most productive clones in dried conditions. We also highlight the need to larger scale regional experiments to produce models that can be used in climate change scenarios.
Keywords: Hybrid poplar; Short rotation coppice; Aridity index; Water availability; Above ground biomass